Blue Carbon release by bottom trawling in the Malaga Bay. (SW Mediterranean) - Muñoz Muñoz, Maria; López-Figueroa, Félix; Reul, Andreas; Bautista-Bueno, Begoña (My University, 2022)
The capture and store a of carbon in coastal and marine ecosystem is referred to as blue carbon storage. Conservation, maintenance and estimation of carbon storage in marine ecosystem is a key issue for climate change scenarios. While conservation of blue carbon ecosystems such as mangroves, tidal marshes and seagrasses, have been accorded worldwide, little information about carbon release from marine ecosystem due to human activity is available. While the Intergovernmental Panel on Climate Change IPCC considers world-wide estimation of carbon sequestration to the seafloor by the biological pump, little is known on the carbon release from the seafloor by sediment disturbing activities, such as bottom trawling. Due to its importance as nursery area, Malaga Bay (Southern Spain) has been proposed by the FAO as an Essential Fish Habitat (GFCM, 2019) suggesting reduction of fishing pressure. Apart of the protection of important nursery area, the reduction of bottom trawling reduces carbon release from the seafloor by sediment disturbance. This reduction of CO2 emission could be considered in the blue carbon market. For this reason, we show a first estimate of CO2 release of bottom trawler >15m in Malaga, and discuss the results in the framework of local Marine Spatial Planning approaches.
Poster Presentation
Keywords: Recursos marítimos; Extractive fishery; Bottom trawling; Bottom Released Carbon; Marine Spatial Planning; Blue Economy